2005
DOI: 10.1111/j.1600-051x.2005.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Ridge alterations following implant placement in fresh extraction sockets: an experimental study in the dog

Abstract: Marked dimensional alterations had occurred in the edentulous ridge after 3 months of healing following the extraction of the distal root of mandibular pre-molars. The placement of an implant in the fresh extraction site obviously failed to prevent the re-modelling that occurred in the walls of the socket. The resulting height of the buccal and lingual walls at 3 months was similar at implants and edentulous sites and vertical bone loss was more pronounced at the buccal than at the lingual aspect of the ridge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
682
11
26

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 679 publications
(772 citation statements)
references
References 15 publications
53
682
11
26
Order By: Relevance
“…The portion of the bone in which the periodontal ligament is attached is known as bundle bone. The crestal portion of the buccal and lingual bone plates is mostly comprised by cortical bundle bone (Araújo et al 2005). Once a tooth is removed, bundle bone resorbs due to the lack of vascular supply and function and a reduction in height and width of the buccal plate takes place.…”
Section: Influence Of Buccal Bone Plate Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…The portion of the bone in which the periodontal ligament is attached is known as bundle bone. The crestal portion of the buccal and lingual bone plates is mostly comprised by cortical bundle bone (Araújo et al 2005). Once a tooth is removed, bundle bone resorbs due to the lack of vascular supply and function and a reduction in height and width of the buccal plate takes place.…”
Section: Influence Of Buccal Bone Plate Thicknessmentioning
confidence: 99%
“…However, clinical and experimental evidence has shown that a reduction in height and width will still occur Araújo et al 2005Araújo et al , 2006. From an aesthetic point of view, these dimensional changes may lead to midfacial recession in the long term (Chen & Buser 2014).…”
Section: Introductionmentioning
confidence: 99%
“…En este caso, en particular, tal y como se ha descrito anteriormente, nos limitamos sólo al empleo de injerto particulado sin aislamiento alguno. Araújo y cols., en 2008 determinaron que el empleo de biomaterial para estos casos tenía la ventaja de generar una menor morbilidad y mayor capacidad para mantener los tejidos blandos minimizando la reabsorción inherente a los procesos de remodelado óseo (26)(27)(28). Las técnicas y materiales utilizados en regeneración ósea guiada son diferentes según el tipo y la localización del defecto clasificándolos en generalizados cuando afectan amplios segmentos y localizados cuando afectan a una hemiarcada o al espacio comprendido por uno o varios dientes, así como los defectos óseos periimplantarios tipo dehiscencias y fenestraciones (29,30).…”
Section: Discussionunclassified
“…Immediate placement techniques, performed in the hope that the functional stimulation provided by the implant would prevent alveolar bone resorption, have been widely recommended in recent years. In the first years of this century, the research of Araujo, among others (27) , made it very clear that this assumption was wrong. Similarly, it is claimed that the immediate provisionalization of the implant placed right after extraction will maintain the position of the marginal gingiva unchanged, since placing an artificial crown that supports the soft tissues will prevent them from collapsing.…”
Section: Figmentioning
confidence: 99%
“…En los últimos tiempos se preconizó mucho la técnica del implante inmediato post extracción con la esperanza de que el estímulo funcional del implante evitaría la reabsorción del hueso alveolar. En los primeros años de este siglo los estudios de Araujo (27) , entre otros, dejaron bien en claro que esa suposición era errónea. De forma similar se sostiene que la provisionalización inmediata del implante inmediato post extracción va a mantener incambiada la posición de la encía marginal, dado que el colocar una corona artificial que sostenga los tejidos blandos va a evitar el colapso de los mismos.…”
unclassified